Research on Shape Change of Multimaterial Electrode for EDM - Wenjian Wang; Yu Liu; Wenchao Zhang; Fujian Ma; Dapeng Yang; Shengfang Zhang (Advances in Materials Science and Engineering)
The shape change law of a multimaterial electrode in EDM was studied, and a cosimulation between ANSYS and MATLAB of electrode shape change of the multimaterial electrode and workpiece was established. Element birth and death in ANSYS was used to obtain the removal volume in a single-pulse discharge, and the electrode feed strategy, material removal, and renewal strategy are considered to establish the shape simulation strategy. Then, a program based on MATLAB software was compiled to simulate the machining process and predict the shape change of the multimaterial electrode of different combinations. The experiments of different multimaterial electrodes were carried out with the die steel as the workpiece. The simulation results were compared with the experimental results to verify the effectiveness of the simulation model.